2020
DOI: 10.1017/gmh.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Depression among TB patients and associated factors in Kathmandu Valley, Nepal

Abstract: Introduction When tuberculosis (TB) and depression co-occur, there is greater risk for comorbidities, disability, suffering, and health-related costs. Depression is also associated with poor treatment adherence in patients with TB. The major aim of this study was to assess the symptoms of depression and associated factors among TB patients currently receiving directly observed treatment short-course (DOTS) treatment. Methods A cross-sectional study was conducted among TB patients current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Fourth, we found few patients with mental health disorders in contrast to a systematic review that identified mental health disorders in nearly a quarter of TB patients [ 8 ]. Anxiety and depression seem to be particularly common if patients are properly screened [ 23 , 24 ]. In our study we did not use a systematic screening tool such as the validated Patient Health Questionnaire (PHQ-9) [ 25 ] and it is likely that we underestimated the prevalence of mental health disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we found few patients with mental health disorders in contrast to a systematic review that identified mental health disorders in nearly a quarter of TB patients [ 8 ]. Anxiety and depression seem to be particularly common if patients are properly screened [ 23 , 24 ]. In our study we did not use a systematic screening tool such as the validated Patient Health Questionnaire (PHQ-9) [ 25 ] and it is likely that we underestimated the prevalence of mental health disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with a study randomly controlled trial showing that ACT could reduce patients’ depression during their treatment. 24 Depression in clients with tuberculosis can be influenced by various factors, including side effects of treatment, low levels of education, smoking and alcohol, and separation (divorce). The results of this study indicate that as many as 70.9% of MDR-TB patients do not work.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with data showing men in Botswana are more likely to smoke than women (Ritchie, 2019). Patients diagnosed with TB have reported both depressive symptoms (Rizvi, 2016; Shrestha et al, 2020) and smoking during treatment of TB (Altet et al, 2017; Leung et al, 2015), with both potentially leading to reduced treatment success. In addition to the hypothesis that this relationship could be bidirectional, another hypothesis for the association between depressive symptoms and smoking is the desire to self-medicate.…”
Section: Discussionmentioning
confidence: 99%